2009
DOI: 10.3109/03639040903386690
|View full text |Cite
|
Sign up to set email alerts
|

Perphenazine solid dispersions for orally fast-disintegrating tablets: physical stability and formulation

Abstract: It was found that 1/5 PPZ/PEG was the most stable dispersion under elevated temperature and/or humidity. FDTs containing 60% of mannitol, 15% of calcium silicate, 15% of crospovidone, and 10% of 1/5 PPZ/PEG solid dispersion exhibited fast disintegration times (37 +/- 3), sufficient hardness (1.28 +/- 0.06 MPa), and fast onset of drug dissolution (34% of PPZ dissolved in 4 minutes), and these properties were found to be retained with storage. Thus, by optimizing the drug/excipient ratio of the solid dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Hence, to develop a tablet of an amorphous solid dispersion of sufficient tensile strength and short disintegration time (<30 min), extragranular components with good compactibility and disintegration properties are required to be included in the formulation. However, limited published reports have conducted systematic studies to identify formulation composition requirements to develop immediate release solid dispersion tablets with acceptable drug product properties (20)(21)(22)(23). To develop orally disintegrating tablets of ibuprofen solid dispersion prepared by HME process, Gryczke et al evaluated various grades and level of crospovidone and croscarmellose sodium, which resulted in development of tablets with short disintegration time and acceptable hardness (21).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to develop a tablet of an amorphous solid dispersion of sufficient tensile strength and short disintegration time (<30 min), extragranular components with good compactibility and disintegration properties are required to be included in the formulation. However, limited published reports have conducted systematic studies to identify formulation composition requirements to develop immediate release solid dispersion tablets with acceptable drug product properties (20)(21)(22)(23). To develop orally disintegrating tablets of ibuprofen solid dispersion prepared by HME process, Gryczke et al evaluated various grades and level of crospovidone and croscarmellose sodium, which resulted in development of tablets with short disintegration time and acceptable hardness (21).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional tablets consisting of PB and lactose were prepared by the method described above 5,19 . The concentrations of PB used were 1, 2, 3, 4, and 5 mg/tablet.…”
Section: Determination Of Bitterness Thresholdmentioning
confidence: 99%
“…On the other hand, the commonly used techniques to improve the drug bitter taste in solid formulations, such as complexation 17 , micronization 14,18 , and the formation of solid dispersions (SDs) 6,19,20 , are not suitable for the highly bitter, highly water soluble drug of PB, either.…”
Section: Introductionmentioning
confidence: 99%
“…This was considered as the sign of molecular level dispersion formation. A subsequent SAXS study of the effect of storage at elevated humidity showed unaltered size of clusters pointing to the retention of molecular miscibility (Laitinen et al 2010). …”
Section: Molecular Miscibility In Asd Using Pxrd and Computational Anmentioning
confidence: 99%